The information content of the yield spread about future inflation in South Africa - Manqoba Ntshakala; Laurence Harris (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The proposition that inflation expectations can be extracted as inflation predictions from the government bond yield curve has been tested, with partially positive results, using data from the United States and European countries. Despite the abundance of empirical studies of the proposition, relatively few of these studies relate to emerging markets, as most emerging markets lack bond markets with the liquidity, breadth, information availability, and range of maturities that would permit such studies. South Africa's highly developed capital markets do have such characteristics, warranting this study's examination of the proposition's validity for South Africa. Using South African time series data, we find strong evidence for the proposition that the slope of the yield curve, measured as a long- to short-term spread, contains information on the future path of inflation. Examining the sub-periods separated by the adoption, in 2000, of inflation targeting, we find that the monetary policy regime shift strengthened the relationship between the yield spread and future inflation. The results suggest that the yield spread can be used by policy makers and the private sector to help forecast inflation in South Africa.
Keywords: E31; E37; E52; G12; 330; expectations; inflation; monetary policy; South Africa; term structure; yield spread